Microbial plankton configuration in the epipelagic realm from the Beagle Channel to the Burdwood Bank, a Marine Protected Area in Sub-Antarctic waters - Guinder, Valeria Ana; Malits, Andrea; Ferronato, Carola; Krock, Bernd; Garzon Cardona, John Edison; Martínez, Ana (PLOS ONE)
Marine microbial plankton hold high structural and functional diversity, however, highresolution data are lacking in a large part of the Global Ocean, such as in subpolar areas of the SW Atlantic. The Burdwood Bank (BB) is a submerged plateau (average depth 100 m) that constitutes the westernmost segment of the North Scotia Ridge (54°-55°S; 56°-62°W). The BB hosts rich benthic biodiversity in low chlorophyll waters of the southern Patagonian Shelf, Argentina, declared NamuncuráMarine Protected Area (NMPA) in 2013. So far, the pelagic microorganisms above the bank have not been described. During austral summer 2016, we assessed the microbial plankton (0.2-200 μm cell size) biomass and their taxonomical and functional diversity along a longitudinal transect (54.2-55.3°S, 58-68°W) from the Beagle Channel (BC) to the BB, characterized by contrasting hydrography. Results displayed a marked zonation in the composition and structure of the microbial communities. The biomass of phytoplankton >5 μm was 28 times higher in the BC, attributed mainly to large diatom blooms, than in oceanic waters above the BB, where the small coccolithophore Emiliania huxleyi and flagellates <10 μm dominated. In turn, the biomass of microheterotrophs above the BB doubled the biomass in the BC due to large ciliates. Notably, toxic phytoplankton species and their phycotoxins were detected, in particular high abundance of Dinophysis acuminata and pectenotoxins above the bank, highlighting their presence in open subpolar regions. Picophytoplankton (<2 μm), including Synechococcus and picoeukaryotes, were remarkably important above the BB, both at surface and deep waters (up to 150 m). Their biomass surpassed by 5 times that of phytoplankton > 5 μm, emphasizing the importance of small-sized phytoplankton in low chlorophyll waters. The homogeneous water column and high retention above the bank seem to favor the development of abundant picophytoplankton and microzooplankton communities. Overall, our findings unfold the plankton ...